Counselling Needs Assessment of Students of WA Polytechnic in The Upper West Region, Ghana - Abubakar, Ayamba Iddrisu; Gyeyir, Felicio Timyang; Adangabe, Amos Amuribadek (South Asian Journal of Social Sciences and Humanities, 2022)
Individuals may seek counselling for various reasons, however, whatever the reason may be,  clients seek counselling in order to be able to address certain issues they may be faced in their  lives. The study is about the counselling needs of students in the Polytechnic in the Wa  Municipality. The data was analysed using both descriptive (frequencies and percentages) and  inferential statistics (Independent t-test and One-Way ANOVA). The findings revealed that, there  were significant differences in age concerning students’ ratings and needs for guidance and  counselling in services. The study revealed that, students needed guidance and counselling as there  were challenged in terms of time allocation problems, inability to discuss with lecturers about their  problems, coping with workload issues as well as struggling to meet deadlines. Due to the absence  of guidance and counselling services, the results of the study led the researchers to the conclusion  that students attending Wa Polytechnic were facing a number of challenges that need answers in  order to be resolved. Based on the findings and conclusion drawn from the study is recommended  that the defunct guidance and counselling unit should be revived and properly resourced for  students to benefit from it.
Keywords: Counselling; needs; assessment; polytechnic; WA